1990
DOI: 10.1161/01.str.21.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation factors and the increased risk of stroke in nonvalvular atrial fibrillation.

Abstract: We studied whether hemostatic abnormalities contribute to the increased risk of stroke in patients with nonvalvular atrial fibrillation. Hemostatic function was studied in four agematched groups: 20 patients with nonvalvular atrial fibrillation and a previous ischemic stroke, 20 patients with nonvalvular atrial fibrillation without a previous stroke, 20 stroke patients with sinus rhythm, and 40 healthy controls. Both groups with nonvalvular atrial fibrillation had significantly higher concentrations of von Wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
117
4
5

Year Published

2002
2002
2007
2007

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(135 citation statements)
references
References 41 publications
(26 reference statements)
5
117
4
5
Order By: Relevance
“…8 The annual incidence of stroke is six times higher in patients with AF than in those with normal sinus rhythm. 1 Atrial fibrillation is associated with an elevation of procoagulant factors in the blood 9 and provides the possibility for thrombi to form in the left atrium when regular effective mechanical contractions are absent. Another related group of patients, who may also be at risk for stroke, are patients with atrial flutter.…”
Section: Risk Of Stroke With Atrial Fibrillationmentioning
confidence: 99%
“…8 The annual incidence of stroke is six times higher in patients with AF than in those with normal sinus rhythm. 1 Atrial fibrillation is associated with an elevation of procoagulant factors in the blood 9 and provides the possibility for thrombi to form in the left atrium when regular effective mechanical contractions are absent. Another related group of patients, who may also be at risk for stroke, are patients with atrial flutter.…”
Section: Risk Of Stroke With Atrial Fibrillationmentioning
confidence: 99%
“…1,2 Most strokes in AF patients, one of the major reasons for hospitalisation in this group, 3 are believed to be cardioembolic, caused by embolism of left atrial thrombi. 4 Thrombus formation in the left atrium could result from decrease in blood flow, 5 increase in blood coagulability, 6 and also endocardial dysfunction in the left atrium. 7 Several recent experimental reports including ours have demonstrated that AF per se causes atrial endocardial dysfunction, which is manifested by reduced endothelial nitric oxide synthase (eNOS), increased expression of plasminogen inhibitor-1 (PAI-1) and also decreased expression of tissue factor pathway inhibitor (TFPI) and thrombomodulin (TM) in the left atrial endocardium, leading to local coagulation imbalance on the internal surface of the atrium.…”
Section: Introductionmentioning
confidence: 99%
“…2 Decreased blood flow with hypercoagulable state in the left atrium has been attributed to the likelihood of clotting formation in the fibrillating atria, as demonstrated in many previous studies. 3,4 In vascular thrombi, however, endothelial dysfunction is also known to play a significant role in addition to the decreased blood flow and hypercoagulability, as shown in the well-known Virchow's triad. Likewise, we could hypothesize that atrial endocardial cells could prevent local thrombus formation under normal conditions and that AF might produce the endocardial dysfunction contributing to the local thrombogenesis, besides the deterioration in the blood flow and coagulability.…”
mentioning
confidence: 99%